2022
DOI: 10.3390/insects13050428
|View full text |Cite
|
Sign up to set email alerts
|

Development, Survival and Reproduction of Spodoptera frugiperda (Lepidoptera: Noctuidae) Fed an Artificial Diet or on Cotton, Castor Bean and Corn Leaves

Abstract: The polyphagy of Spodoptera frugiperda (Lepidoptera: Noctuidae) renders its control difficult because variations in the phenology of host plants grown in different seasons of the year and near each other can facilitate the movement of this pest between crops. The objective of this work was to examine certain biological characteristics of S. frugiperda fed on an artificial diet or on cotton, castor bean, or corn leaves. The experimental design was in randomized blocks, with four treatments represented by S. fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…But on the contrary, Salem et al, 2021 indicated that the larval duration was not, significantly, different after feeding larvae on maize or castor bean leaves as it was 23.36 and 23.58 days on castor bean and maize, respectively. Also, on similar studies Ramos et al, (2022) recorded the shortest duration of the larval stage of S. frugiperda (16.73 days) after rearing on maize comparing with cotton (25.18 days) and castor bean (21.43 days) at 25 ± 2˚C, relative humidity of 60 ± 10 under laboratory conditions.…”
Section: Larval Stagementioning
confidence: 57%
See 1 more Smart Citation
“…But on the contrary, Salem et al, 2021 indicated that the larval duration was not, significantly, different after feeding larvae on maize or castor bean leaves as it was 23.36 and 23.58 days on castor bean and maize, respectively. Also, on similar studies Ramos et al, (2022) recorded the shortest duration of the larval stage of S. frugiperda (16.73 days) after rearing on maize comparing with cotton (25.18 days) and castor bean (21.43 days) at 25 ± 2˚C, relative humidity of 60 ± 10 under laboratory conditions.…”
Section: Larval Stagementioning
confidence: 57%
“…Gamil (2020) demonstrated that the pre-oviposition, oviposition and post-oviposition periods of S. frugiperda females reared during their larval stage on castor beans were 3.5, 5.11 and 2.61 days, respectively, with a mean duration of 11.22 days for female and 13 days for male, and recorded that egg productivity reached 1787.5 eggs on castor leaves. Ramos et al, (2022) indicated that the pre-oviposition, oviposition and post-oviposition periods and fecundity (2.11, 4.67, 1.00 days and 663.78 /♀ eggs, respectively) were higher for S. frugiperda females originating from larvae fed on maize leaves, than that originated from larvae fed on cotton (3.00, 2.50, 0.90 days and 312.11 egg/♀, respectively) or castor bean leaves (3.70, 2.40, 0.90 days and 216.63 egg/♀).…”
Section: Larval Stagementioning
confidence: 99%
“…Then, each egg mass attached to plastic paper was placed in a petri dish (diameter = 10.5 cm, height = 2.5 cm) containing a piece of artificial diet that was made from Greene et al’s method [ 48 ]. The larvae were reared individually when they reached the third instar in 12-well plastic plate until they emerged as adults [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…Artificial diets can provide cheap and high-quality test insect diets [9]. Mass rearing of highquality and cheap test insects is still under development, especially artificial diets for S. frugiperda [1,10]. Artificial diets must contain primary compounds such as protein and secondary compounds in the IOP Publishing doi:10.1088/1755-1315/1346/1/012001 2 form of the olfaction of the host plant leaves [11].…”
Section: Introductionmentioning
confidence: 99%